The jet energy scale uncertainty derived from Gamma-jet events for small and large radius jets and the calibration and performance of variable R Jets with the ATLAS Detector - Kogan, L (2014)
In this thesis the jet energy scale uncertainty of small and large radius jets at the ATLAS detector is evaluated in-situ using gamma-jet events. The well calibrated photon in the gamma-jet events is used to probe the energy scale of the jets. The studies of the jet energy scale of small radius jets are performed using 4.7 fb-1 of data collected at sqrts = 7 TeV in 2011. The gamma-jet methods which were developed are then adapted and applied to large radius jets, using 20.3 fb^-1 of data collected at sqrts = 8 TeV in 2012. The new jet energy scale uncertainties are found to be ~1 % for |eta| < 0.8, rising to 2-3 % for |eta| > 0.8. These uncertainties are significantly lower than the 3-6 % precision which has previously been achieved at ATLAS using track jets as a reference object. Due to the increase in precision, uncertainties due to pile-up and the topology of the jet also had to be evaluated. The total energy scale uncertainties for large radius jets are reduced by ~1-2 % (0.5-1 %) for |eta| < 0.8 (> 0.8). This reduction will be beneficial to analyses using large radius jets and it is specifically shown to benefit the t-tbar resonance search in the semi-leptonic channel. The t-tbar search looks for events with two top quarks in the final state, where one decays leptonically and the other hadronically. The hadronically decaying top quark is reconstructed using a large radius jet, and the jet energy scale uncertainty is a dominant source of uncertainty in the analysis. In addition to the studies of the jet energy scale of large radius jets, the first derivation of a calibration, and jet energy scale uncertainties derived with gamma-jet events, are shown for Variable R jets. The Variable R jet algorithm is a new type of jet algorithm with a radius that is inversely proportional to the size of the jet, making it useful for the study of high momentum top quarks. It is shown that similar methods can be used to calibrate and assess the uncertainties of Variable R jets as are used for standard, fixed radius jets at the ATLAS detector, although some adaptations will be necessary. The studies provide a basis for the calibration of Variable R jets in the future.